Analisis Indeks Kepuasan Masyarakat (IKM) terhadap Program CSR Pemberdayaan UMKM Cahaya Bulam Bakery: Studi Kasus PT PLN Indonesia Power UBP Barru (International Forum of Researchers and Lecturers, 2025)
Corporate Social Responsibility (CSR) programs represent a form of social and environmental accountability implemented by companies as a contribution to sustainable development. In the context of PT PLN Indonesia Power UBP Barru, CSR implementation is realized through community-based economic empowerment initiatives focusing on Micro, Small, and Medium Enterprises (MSMEs), particularly the Cahaya Bulam Bakery MSME. This study aims to assess the level of community satisfaction with the quality of CSR program implementation using the Community Satisfaction Index (IKM) approach as stipulated in the Regulation of the Minister for Administrative and Bureaucratic Reform (Permenpan RB) No. 14 of 2017. The research employed a quantitative approach with a survey method involving all program beneficiaries. Data were collected using a questionnaire with a four-point Likert scale covering 20 assessment indicators, including program relevance, community participation, communication, innovation, and sustainability. The findings reveal that the CSR program of Cahaya Bulam Bakery achieved an IKM score categorized as “Excellent,” with a conversion value of 94.13. This indicates that the program has been effectively implemented in enhancing beneficiary capacity, generating economic impact, and strengthening synergy between the company and the local community. Nevertheless, there remains room for improvement, particularly in ensuring fairness and enhancing the program’s relevance to community needs.